Peaceful journalism in reporting conflict in Papua on the news portals - Sonni, Alem Febri; Irwanto, Irwanto; Malau, Maldhi Hamonangan (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
The aims of this study are to describe the framing and journalism of peace conducted by the media portals Suarapapua.com and Kompas.com and the framing and journalism of peace reporting on the conflict in Papua. This research was conducted for approximately 3 months, from May to July 2022. The method used in this study is a qualitative method using framing analysis by Robert E. Entman, namely, the selection of issues and highlighting certain aspects of reality or issues. The results of the analysis are presented in the form of the Entman model, then reviewed from the perspective of Johan Galtung's Peaceful Journalism. The results of this study indicate that the framing carried out by Suarapapua.com and Kompas.com has an impact on maintaining security stability in Papua. And the application of peace journalism carried out by both of them provides prevention of the ongoing adverse effects on conflicting groups in Papua.